1984
DOI: 10.1042/bj2190451
|View full text |Cite
|
Sign up to set email alerts
|

Collagen composition of normal and myxomatous human mitral heart valves

Abstract: The collagens were studied in 13 normal and 19 myxomatous human mitral valves. The collagens of the valve were completely solubilized by using a method consisting of guanidinium chloride extraction, limited pepsin digestions and CNBr cleavage of the residue. The normal valves contained 74% type I, 24% type III and 2% type V collagen. The type I and type III collagens had similar solubility patterns, although only type I collagen was detected in the guanidinium chloride extract. Type V collagen was only detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
98
0
5

Year Published

1989
1989
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(109 citation statements)
references
References 33 publications
6
98
0
5
Order By: Relevance
“…[11][12][13] In some cases, there is an identified genetic and congenital defect in the connective tissue, such as in Marfan syndrome. [14][15][16][17] Recent studies have demonstrated that mucopolysaccharide was abnormally accumulated and immune activity against extracellular matrix proteins (such as fibrin and elastin 18) and collagen I and III 19) …”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] In some cases, there is an identified genetic and congenital defect in the connective tissue, such as in Marfan syndrome. [14][15][16][17] Recent studies have demonstrated that mucopolysaccharide was abnormally accumulated and immune activity against extracellular matrix proteins (such as fibrin and elastin 18) and collagen I and III 19) …”
Section: Discussionmentioning
confidence: 99%
“…33) In another study, the concordance between inadequate production of type III collagen and echocardiographic findings of MVP in patients with type IV Ehler-Danlos syndrome have suggested that this collagen abnormality may be the responsible factor in patients with this syndrome. 34) Abnormalities of collagen have been found in myxomatous or floppy valves of patients with MVP [11][12][13] that coincide with those identified in skin biopsies of patients with hypermobility syndrome 9) leading to the suggestion of a common pathogenetic mechanism of abnormal production or maturation of collagen. 14) Several clinical observations have led to the speculation that primary MVP syndrome represents a generalized disorder of connective tissue.…”
Section: )mentioning
confidence: 99%
“…6) In the following years, a high incidence of MVP has been reported in patients with benign joint hypermobility syndrome (BJHMS), 7,8) which, like MVP, is inherited mainly as a sex-influenced dominant trait. 9,10) Abnormalities of collagen have been found in myxomatous or floppy valves of patients with MVP [11][12][13] that coincide with those identified in skin biopsies of patients with hypermobility syndrome 9) leading to the suggestion of a common pathogenetic mechanism of abnormal production or maturation of collagen. 14) However, there have been a few studies on the relation between the echocardiographic features of mitral valves [anterior mitral leaflet thickness (AMLT), 15) maximal leaflet displacement (MLD), 7) degree of mitral regurgitation (DMR)], elastic properties of the aortic wall [index of aortic systolic (AOSDI) and diastolic diameters (AODDI), index of aortic stiffness (IAOS) and aortic distensibility (AOD)], and Beighton hypermobility score (BHS) in MVP patients with BJHMS.…”
mentioning
confidence: 99%
“…37 These tissue level changes cause MV leaflets with myxomatous disease to become thickened and enlarged, and the redundant tissue of these leaflets leads to poor leaflet coaptation and MR. 37 Morphologic analysis of myxomatous MVs has shown a greater than two-fold increase in valve surface area, due to significant increases in both the anterior and posterior leaflet surface areas. 25 Additionally, the structural elements of the MVcollagen, elastin, and proteoglycans -constitute approximately 85-95% of leaflet dry weight, 7,28 indicating that alteration of these components will significantly affect leaflet mechanical properties. Myxomatous leaflets have previously been shown to be more extensible and less than half as strong as normal leaflets, further contributing to leaflet prolapse and MR. 5 Similar enlargement and extensibility changes can also occur in the chordae tendineae, in which the chords become thickened and elongated, leading to leaflet billowing into the atrium during systole.…”
Section: Mvp Due To Degenerative Mrmentioning
confidence: 99%